Penerapan Arsitektur Eco-Tech pada Desain Gedung Olahraga di Kota Palopo - Ria, Jawariah; AS, Zulkarnain; Alfiah, Alfiah (TIMPALAJA : Architecture Student Journals, 2025)
The quality of the facilities and infrastructure of the Lagaligo Sports Hall (GOR) in Palopo City is not yet optimal in terms of capacity, comfort, and building environmental performance. This condition not only fails to reflect the principles of sustainable building but also does not fully meet the community's need for sports activities. The purpose of this research is to find ways to renovate the Lagaligo Sports Hall using an eco-tech architectural approach. This approach has the potential to improve the function, energy efficiency, and environmental quality of the sports area. The method used is descriptive-qualitative, with field observation of the current site and building conditions, literature research on eco-tech theory and sports infrastructure standards, and a comparative analysis between current conditions and design criteria. The design results show that eco-tech principles are applied in several key aspects. This includes site development integrated with public open spaces, the use of skylights and building envelopes that optimize natural lighting and ventilation, the implementation of solar panels and rainwater harvesting systems, and the creation of more efficient interior layouts for athletes, spectators, and managers. This redesign led to the idea of a more energy-efficient sports hall suited to the tropical climate. Additionally, it enhances the comfort and quality of the sports environment for Palopo's residents Energy.